Preoperative adaptation of allogeneic bone graft using a stereolithographic model: case report of a fixed complete denture - S. Longoni; L. Dusi; A. Baldini; S.G. Marino; M. Sartori (Ariesdue, 2013)
Aim To replace an adequate bone volume for the implant placement in presence of a severe maxillary atrophy reducing intraoperative times and postoperative morbidity.Materials and methods After a diagnostic waxing up aimed at identifying the bone volumes to be regenerated for implant placement, a stereolithographic model (obtained from a computed tomography) was used for adapting an iliac crest allogeneic block. The 6-part division of the block was performed using templates. The obtained bone blocks were shaped to obtain an ideal morphology, at the closest contact possible with the receiving atrophic bone crest. Six months later eight implants were placed at second-stage surgery and a fixed complete denture was made after 4 months.Results At the second-stage surgery, the mean overall bone ridge horizontal increase was 4.8±0.2 mm, whereas the mean bone blocks resorption was of 0.9±0.1 mm (18.75%). A follow-up three years later revealed that the implants survival was 100% and the patient did not have any major complaint. Clinical, radiographic and histologic results confirm that allogeneic bone graft may be a valid alternative to autologous bone graft.Conclusions Allogeneic bone blocks may represent a viable alternative for ridge restoration in presence of severe atrophy of the jaws. Nevertheless, various factors including suitable blood supply, the thickness and quality of the receiving bone crest and the perfect closure of the soft tissues, are to be taken into account regarding graft integration.